Intra versus interprofessional conflicts: implications for conflict management training. Issue 2 (3rd March 2020) - Bajwa, Nadia M.; Bochatay, Naïke; Muller-Juge, Virginie; Cullati, Stéphane; Blondon, Katherine S.; Junod Perron, Noëlle; Maître, Fabienne; Chopard, Pierre; Vu, Nu V.; Kim, Sara; Savoldelli, Georges L.; Hudelson, Patricia; et al.
ABSTRACT: Interprofessional collaboration and conflict management training are necessary in health sciences curricula. Characteristics of conflicts occurring within intraprofessional or between interprofessional teams can vary and are poorly understood. We sought to compare and contrast characteristics of intra- versus interprofessional conflicts to inform future training programs. An exploratory study was conducted through semi-structured interviews with 82 healthcare professionals working in a tertiary hospital. Interviews focused on sources, consequences, and responses to conflicts. Conflict situations were analyzed with conventional content analysis. Participants shared more intra- than interprofessional situations. Intraprofessional conflicts were caused by poor relationships, whereas interprofessional conflicts were associated with patient-related tasks and social representations. Avoiding and forcing were the most commonly mentioned responses to intraprofessional conflicts. The theme of power impacted all aspects of conflict both intra- and interprofessional. Intraprofessional conflicts were found to be as important as interprofessional conflicts. Differences in the sources of conflict and similarities regarding consequences of and responses to conflicts support integration of authentic clinical situations in interprofessional training. Understanding similarities and differences between intra- and interprofessional conflicts may help educators develop conflict management training that addresses the sources, consequences, and responses to conflicts in clinical settings.